Sars-Cov-2 spike protein and plasma from COVID-19 patients induce extracellular traps by myeloid-derived suppressor cells - Grassi, Germana; Gili, Simona; Casetti, Rita; Percario, Zulema Antonia; Tumino, Nicola; Vacca, Paola; Lamsira, Harpreet Kaur; Nardacci, Roberta; Notari, Stefania; Bordoni, Veronica; Cimini, Eleonora; Cristofanelli, Flavia; et al. (Frontiers in Cellular and Infection Microbiology, 2025)
IntroductionPolymorphonuclear-myeloid-derived suppressor cells (PMN-MDSC) are elevated in COVID-19 patients, playing a crucial role in suppressing the SARS-CoV-2 specific T-cell response and serving as an early marker for disease progression. In this study, we investigated the involvement of PMN-MDSC from COVID-19 patients in the formation of extracellular traps (ET).MethodsFifty RT-PCR–confirmed severe COVID-19 patients admitted to the ICU and ten healthy donors were enrolled. PBMC were isolated from peripheral blood by density gradient centrifugation, and PMN-MDSC frequency was evaluated by flow cytometry. PMN-MDSC were isolated by immunomagnetic separation. ET extrusion was analyzed by immunofluorescence imaging. Apoptosis of pulmonary microvascular endothelial cells cultured with PMN-MDSC was measured by flow cytometry.ResultsWe found that platelet-rich plasma (PRP) from COVID-19 patients, unlike that from healthy donors, induced ET formation by PMN-MDSC. Furthermore, the PRP-induced ET was found to be independent of Toll-like receptor 4 (TLR4) signaling. Interestingly, the SARS-CoV-2 Spike protein itself can trigger ET formation via a TLR4-dependent pathway. Additionally, PMN-MDSC induced endothelial cell apoptosis through an ET-independent mechanism.DiscussionThese findings highlight a previously unrecognized contribution of PMN-MDSCs to the thrombotic complications in severe COVID-19 cases, underscoring their detrimental impact on disease progression.